Penguatan Peran Guru BK dalam Membangun Ketahanan Emosional Remaja di Tengah Tantangan Digital - Handayani, Arri; Fitriana, Siti; Kusdaryani, Wiwik; Ricky Rozzaqi , Ade (Wahana Dedikasi: Jurnal PkM Ilmu Kependidikan, 2025)
The advancement of digital technology brings significant benefits to life but also creates serious challenges for adolescents’ mental health. Adolescents have become increasingly vulnerable to cyberbullying, social media addiction, and social pressures that harm their emotional well-being. However, many Guidance and Counseling (BK) teachers still possess a limited understanding of digital issues and have not optimized their roles in strengthening adolescents’ emotional resilience. This limitation weakens the effectiveness of school counseling services in helping students address mental health problems caused by digital technology. To address this issue, this community service program provided a solution through training for BK teachers. The program attempted to enhance their understanding of digital issues and their impact on adolescents’ mental health, optimize the role of BK teachers in building emotional resilience through simulations, and assist them in developing Service Implementation Plans (RPL) that incorporate Social-Emotional Learning (SEL) elements. The training used lectures, group discussions, simulations, practice, and Q&A sessions. This program ran for two weeks, covering planning, implementation, and evaluation stages. The training successfully improved BK teachers’ abilities to provide more effective counseling services for students, helping adolescents maintain emotional resilience amid rapid digital advancements. Pre-test and post-test results indicate a 30.1% average increase in understanding scores, demonstrating the training’s effectiveness.